2021
DOI: 10.3390/life11101052
|View full text |Cite
|
Sign up to set email alerts
|

C1431T Variant of PPARγ Is Associated with Preeclampsia in Pregnant Women

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is essential for placental development, whose SNPs have shown increased susceptibility to pregnancy-related diseases, such as preeclampsia. Our aim was to investigate the association between preeclampsia and three PPARγ SNPs (Pro12Ala, C1431T, and C681G), which together with nine clinical factors were used to build a pragmatic model for preeclampsia prediction. Data were collected from 1648 women from the EDEN cohort, of which 35 women had preeclamptic pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In this study, the analysis of selected genotypes showed that the co-existence of PPAR-γ2 C1431C polymorphism with FAM13A rs1903003 (TT) or rs7671167 (TT), or rs2869967 (CC), was related to higher values of BMI and WHR. Interestingly, variant C1431T of PPAR-γ2 has been associated with obesity [ 52 ], hypertension, and preeclampsia risk [ 65 ]. Conversely, the PPAR-γ2 T1431 variant has opposing associations with body mass [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the analysis of selected genotypes showed that the co-existence of PPAR-γ2 C1431C polymorphism with FAM13A rs1903003 (TT) or rs7671167 (TT), or rs2869967 (CC), was related to higher values of BMI and WHR. Interestingly, variant C1431T of PPAR-γ2 has been associated with obesity [ 52 ], hypertension, and preeclampsia risk [ 65 ]. Conversely, the PPAR-γ2 T1431 variant has opposing associations with body mass [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Holdsworth-Carson et al showed that placental PPARγ mRNA and protein were significantly increased in placentae from women that delivered preterm with co-existing intrauterine growth restriction and preeclampsia [83], while Jia et al noted high PPARγ protein expression levels in preeclamptic placental tissues, with the rs201018 polymorphism in the PPARγ promoter region significantly correlating with the development of preeclampsia [96]. Liu et al showed that the C1431T variant of PPARγ significantly correlates with preeclamptic susceptibility [97]. In addition, Permadi et al exposed primary trophoblastic cells obtained from normal pregnancy to serum from normal pregnancy, early-onset, or late-onset preeclampsia, and highlighted that exposure to serum from only late-onset preeclampsia induced high PPARγ expression [98].…”
Section: The Role Of Pparγ In Preeclampsiamentioning
confidence: 99%
“…Furthermore, a number of gene candidate-based studies of preeclampsia were conducted, resulting in a list of genes associated with the risk [9]. Among the genes reported to be associated with preeclampsia are MTHFR (rs1801133), F5 (rs6025) [10], NOS3 [11], PPARγ [12], ERAP2 [13], STOX1, CORIN, EPHX1, INO80B [14], GSTP1 [15], FGF5 [16], a role for the X chromosome [17] and several other chromosomal regions. According to this set of studies, some genes were found to affect susceptibility to preeclampsia in specific populations [18,19].…”
Section: Introductionmentioning
confidence: 99%